2011
DOI: 10.1007/s00268-011-1155-y
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence after Intended Curative Excision of Presacral Lesions: Causes and Preventions

Abstract: Presacral lesions are likely to be multiple, lobulated, infected, ruptured, and adhesive to the sacrococcyx and rectum, which contribute to the high local recurrence rate. Preoperative CT/MRI/ERUS and careful intraoperative exploration are required to direct surgical treatment and to reduce local recurrence. Optimal selection of surgical approach also is very important to reduce local recurrence. Presacral lesions attached to the sacrococcyx or rectum require simultaneous partial resection of the sacrococcyx o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In studies where complete resections were reported, the rates of recurrence were reported as 0% at 10-year followup in one study 6 , and 6.2% at 5-year follow-up in another. 2 A study by Hjermstad and Helwig 21 reported a recurrence rate of 11.1% during a 11-year follow-up of patients with tailgut cysts, and Gao et al 8 reported 17.9% recurrence in their series of patients with presacral lesions, which are closer to our findings. In addition to the malignancy of the initial tumor, complete excision of the lesion and any involved entity seems to be the most important factor in the prevention of recurrence.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In studies where complete resections were reported, the rates of recurrence were reported as 0% at 10-year followup in one study 6 , and 6.2% at 5-year follow-up in another. 2 A study by Hjermstad and Helwig 21 reported a recurrence rate of 11.1% during a 11-year follow-up of patients with tailgut cysts, and Gao et al 8 reported 17.9% recurrence in their series of patients with presacral lesions, which are closer to our findings. In addition to the malignancy of the initial tumor, complete excision of the lesion and any involved entity seems to be the most important factor in the prevention of recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…14,15 However, whether the coccyx truly causes recurrence remains unknown, and studies have shown that recurrence mostly occurs in malignant tumors and cases where total resection could not be performed. 8,16 The majority of recent studies suggest that the coccyx should not be resected unless the lesion is directly attached to the coccyx. 16,17 In the current study, coccygectomy was performed on 11 (37.9%) patients, and only one (9.1%) of these patients developed recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because revisional surgery for retrorectal tumour is difficult and not optimal, en bloc resection for malignant tumours with the aim of achieving an R0 resection should be the strategy wherever possible. Simultaneous coccygectomy, sacral resection, rectal resection and vaginal resection may be required to achieve this. For benign tumours, adjacent organs do not have to be resected even for recurrent benign tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Primary presacral tumors are relatively rare tumors occurring in the space between the sacrum and the rectum; in 1985, the records at the Mayo Clinic in the USA indicate that presacral lesions occurred in 1 out of 40,000 registrations (1,2). The surgical boundaries of the presacral tumor include the fascia propria of the rectum anteriorly and the presacral fascia posteriorly, while the endopelvic fascia, the bilateral ureter and iliac vessels may also adhere to the tumor (3).…”
Section: Introductionmentioning
confidence: 99%